Modified cellulose and resin composition
The introduction of 3HB modified cellulose fibers into biodegradable resin compositions addresses the limitations of existing technologies by enhancing biodegradability and mechanical properties, particularly under anaerobic conditions, without the need for compatibilizing agents.
Patent Information
- Application Number
- JP2021101077
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-06-17
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2041-06-17
AI Technical Summary
Existing resin compositions for biodegradable plastics lack sufficient biodegradability, especially under anaerobic conditions, and often require compatibilizing agents to improve compatibility with cellulose fibers, which can limit material selection and environmental sustainability.
The development of a resin composition that incorporates 3-hydroxybutyric acid (3HB) modified cellulose fibers, which are biodegradable and do not require a compatibilizing agent, thereby enhancing the biodegradability and mechanical properties of biodegradable plastics.
The modified cellulose fibers improve the interfacial affinity with biodegradable plastics like PHA, leading to enhanced mechanical properties and biodegradability under anaerobic conditions, contributing to reduced carbon footprint and improved environmental sustainability.
Smart Images

Figure 0007650462000003 
Figure 0007650462000004 
Figure 0007650462000005
Abstract
Description
[Technical field]
[0001] The present invention relates to cellulose modified with 3-hydroxybutyric acid (hereinafter sometimes simply referred to as "3HB") or an oligomer thereof, and a resin composition containing this modified cellulose. [Background technology]
[0002] From the viewpoint of environmental conservation and realization of a sustainable society, biomassification of some or all of plastic raw materials is being promoted, and the use of bio-based plastics (or biodegradable plastics) is progressing. From the viewpoint of durability and strength, such plastics are generally used in the form of a resin composition in combination with various additives and reinforcing materials. As reinforcing materials, fibrous reinforcing materials such as carbon fiber and glass fiber are used, but these fibrous reinforcing materials emit a lot of carbon dioxide during the manufacturing process and are poorly recyclable. On the other hand, cellulose, which is a fiber derived from plants, has a small environmental load and is a sustainable resource, and has excellent properties such as a high elastic modulus, high strength, and a low linear expansion coefficient. Therefore, it is required to replace it with plant-derived fibers such as cellulose as a reinforcing material. However, cellulose fibers and cellulose nanofibers, which are nanofibers of cellulose, generally have poor compatibility (affinity, miscibility) with plastics, and a compatibilizer or the like is used in combination.
[0003] JP 2017-171713 A (Patent Document 1) describes a masterbatch that contains acylated modified plant fiber, a thermoplastic resin, and a compatibilizer, and is diluted with a diluting resin, and describes an example in which acetylated modified plant fiber is used as the acylated modified plant fiber, polylactic acid is used as the thermoplastic resin, and polypropylene and polyethylene are used as the diluting resin.
[0004] JP 2016-79369 A (Patent Document 2) describes a modified cellulose that is highly dispersible in resins and is modified with a compound having a 9,9-bisarylfluorene skeleton, and is useful as a material for compounding resins. As resins, biomass-derived aliphatic polyester resins such as polylactic acid are also given as examples.
[0005] Furthermore, if the resin composition contains a component that is partially or entirely non-biodegradable (such as plastics, additives, reinforcing materials, etc.), the non-biodegradable components that flow into the environment, including soil, lakes and rivers, or into the ocean, are broken down and fragmented by ultraviolet rays, etc., to generate microplastics with diameters of 5 mm or less. There is concern that these microplastics, when ingested into the living bodies of birds, fish, etc., may cause endocrine disruption.
[0006] Examples of biodegradable plastics include polylactic acid (PLA), polyhydroxyalkanoate (PHA), polybutylene succinate (PBS), and polycaprolactone (PCL). However, these biodegradable plastics have low biodegradability (or biogasification) under anaerobic conditions and low biodegradability in the ocean. Since the biodegradable plastics have a high density and sink in the ocean, solving the microplastic problem requires the development of plastics that have high biodegradability even in anaerobic conditions such as in the ocean.
[0007] H. Yagi et al., Polymer Degradation and Stability, 110, (2014), 278-283 (Non-Patent Document 1) evaluates the biodegradability of various biodegradable polyesters under anaerobic conditions, and discloses that poly-3-hydroxybutyrate (PHB) exhibits high biodegradability under anaerobic conditions compared to PLA, PCL, and PBS. However, poly-3-hydroxyalkanoates such as PHB produced (biosynthesized) by microorganisms lack the mechanical properties required for general-purpose plastic molded bodies and are also economically inefficient, so they have not been widely used.
[0008] On the other hand, as a biodegradable plastic into which 3HB has been introduced by chemical synthesis, JP 2017-025138 A (Patent Document 3) discloses a biodegradable copolymer in which the ratio of 3-hydroxybutyric acid (3HB) units is 1 to 20 mol% relative to the total constituent units. Patent Document 3 describes that a biodegradable copolymer into which 3HB units have been randomly introduced has high biodegradability under aerobic and anaerobic conditions. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] JP 2017-171713 A [Patent Document 2] JP 2016-79369 A [Patent Document 3] JP 2017-025138 A [Non-patent literature]
[0010] [Non-Patent Document 1] H.Yagi et al., Polymer Degradation and Stability, 110, (2014), 278-283 Summary of the Invention [Problem to be solved by the invention]
[0011] The masterbatch described in Patent Document 1 is suitable for preparing a fiber-reinforced resin composition. However, since the compatibilizer of the masterbatch does not exhibit biodegradability, it is not necessarily sufficient from the viewpoint of sustainable environmental conservation. In particular, if a dilution resin that does not exhibit biodegradability is used, the fiber-reinforced resin composition cannot be expected to be biodegradable. In addition, since each component has a predetermined solubility parameter relationship, there is a risk that the range of material selection will be narrowed. Furthermore, acylated modified plant fibers are not necessarily sufficiently biodegradable, particularly in anaerobic conditions.
[0012] The modified cellulose described in Patent Document 2 has high compatibility with resins, but does not have sufficient biodegradability, and therefore, even if the modified cellulose is added to a biodegradable plastic, the biodegradability of the entire resin composition cannot be improved.
[0013] The biodegradable copolymer described in Patent Document 3 has low reactivity of 3HB and is easily dehydrated intramolecularly by heat or acid, making it difficult to increase the molecular weight and sometimes resulting in insufficient mechanical properties.
[0014] Accordingly, an object of the present invention is to provide a modified cellulose fiber (or modified cellulose fiber) which is formed from a biodegradable component and is useful as a reinforcing material for resins, and a resin composition containing the modified cellulose fiber.
[0015] Another object of the present invention is to provide a modified cellulose fiber (or modified cellulose fiber) that can effectively reinforce biodegradable plastics without necessarily requiring a compatibilizer and is useful as a biodegradable reinforcing material, and a resin composition containing this modified cellulose fiber.
[0016] It is still another object of the present invention to provide a biodegradable resin composition in which all polymer components, including cellulose, are biodegradable even under anaerobic conditions in soil, water including the ocean, and the like. [Means for solving the problem]
[0017] As a result of intensive research to solve the above-mentioned problems, the inventors discovered that 3-hydroxybutyric acid-modified cellulose (3HB-C), in which biodegradable cellulose fibers are modified with 3-hydroxybutyric acid or its oligomers, is formed from biodegradable components and is useful as a reinforcing material for resins, thereby completing the present invention.
[0018] That is, the modified cellulose of the present invention has 3-hydroxybutyric acid or an oligomer thereof bound to cellulose fibers. The modified cellulose may have the 3-hydroxybutyric acid or an oligomer thereof ester-bonded to the 6-position of an anhydroglucose unit of the cellulose fibers. The average degree of polymerization of the 3-hydroxybutyric acid or an oligomer thereof may be 1 to 10. The grafting rate of the 3-hydroxybutyric acid or an oligomer thereof may be 5 to 30 mol %. The 3-hydroxybutyric acid may be R-3-hydroxybutyric acid.
[0019] The present invention also includes a resin composition containing the modified cellulose and at least one resin selected from a thermoplastic resin and a curable resin. The resin may contain a biodegradable plastic. The resin may be a homopolymer or copolymer of at least one monomer selected from a hydroxyalkanoic acid and a lactone. The ratio of the modified cellulose may be 0.1 to 20 parts by mass with respect to 100 parts by mass of the resin.
[0020] The present invention also includes a method for improving the mechanical properties of a resin by blending the modified cellulose with the resin. The resin may be a biodegradable plastic. Effect of the Invention
[0021] In the present invention, the biodegradable cellulose fibers are modified with 3-hydroxybutyric acid or its oligomers, and therefore are formed from biodegradable components and are useful as reinforcing materials for resins.
[0022] In addition, although cellulose-based fillers generally have low affinity with resins, by modifying them with 3HB, their interfacial affinity with polyhydroxyalkanoates (PHAs) such as PHBH is improved. Therefore, in the present invention, a compatibilizer is not necessarily required, and the fillers can effectively reinforce biodegradable plastics, making them useful as biodegradable reinforcing materials.
[0023] Furthermore, as shown in Non-Patent Document 1, PHA (and its monomer 3HA) and cellulose are both rare polymers that are biodegradable even under anaerobic conditions in soil, ocean water, etc. Therefore, by combining 3HB-C and PHA, a biomass filler can be formed that is composed only of components that can be decomposed under anaerobic conditions, which can contribute to low carbon and decarbonization. [Brief description of the drawings]
[0024] [Figure 1] FIG. 1 is a chart showing FT-IR (Fourier transform infrared spectroscopy) of the raw materials used in the examples and the resulting modified cellulose. [Diagram 2] FIG. 2 is a chart of the solid-state 13C-NMR spectrum of the modified cellulose obtained in the examples and comparative examples. [Diagram 3] FIG. 3 is a graph showing the results of the tensile tests on the films obtained in Comparative Examples 1 and 2 and Example 7. [Figure 4] FIG. 4 is a graph showing the results of the tensile test on the films obtained in Comparative Examples 1 and 3 and Example 8. [Diagram 5] FIG. 5 is a graph showing the results of the tensile test on the films obtained in Comparative Examples 1 and 4 and Example 9. [Figure 6] FIG. 6 is a scanning electron microscope (SEM) photograph of the tensile fracture surfaces of the films obtained in Example 8 and Comparative Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0025] [Modified cellulose] The modified cellulose of the present disclosure comprises cellulose fibers and 3-hydroxybutyric acid (3-hydroxybutanoic acid) or an oligomer thereof bonded thereto.
[0026] (Cellulose fiber) Examples of cellulose constituting the cellulose fiber include pulps with low content of non-cellulose components such as lignin and hemicellulose, for example, pulps produced from plant-derived cellulose raw materials {for example, wood [e.g., coniferous trees (pine, fir, spruce, hemlock, cedar, etc.), broad-leaved trees (beech, birch, poplar, maple, etc.)], herbaceous plants [hemp (hemp, flax, Manila hemp, ramie, etc.), straw, bagasse, Mitsumata, etc.], seed hair fibers (cotton linters, bombax cotton, kapok, etc.), bamboo, sugar cane, etc.}, animal-derived cellulose raw materials (such as sea squirt cellulose), and bacterial-derived cellulose raw materials (such as cellulose contained in nata de coco). These celluloses can be used alone or in combination of two or more kinds. Among these celluloses, celluloses derived from wood pulp (e.g., coniferous pulp, broad-leaved pulp, etc.) and seed hair fiber pulp (e.g., cotton linter pulp) are preferred. The pulp may be mechanical pulp obtained by mechanically treating a pulp material, but chemical pulp obtained by chemically treating a pulp material is preferred because it has a low content of non-cellulose components.
[0027] The cellulose may be cellulose (or cellulose fiber) having high crystallinity, and the crystallinity of the cellulose may be, for example, 40 to 100% (e.g., 50 to 100%), preferably 60 to 100%, more preferably 70 to 100% (particularly 75 to 99%), and usually the crystallinity may be 60% or more (e.g., 60 to 98%). In addition, examples of the crystal structure of the cellulose include type I, type II, type III, and type IV, and the type I crystal structure, which is excellent in linear expansion properties and elastic modulus, is preferable. The crystallinity can be measured using a powder X-ray diffractometer (Rigaku Corporation's "Ultima IV"), etc.
[0028] Cellulose fibers (particularly, cellulose nanofibers) have a high cellulose component content (or cellulose purity). The cellulose component content can be selected from the range of about 60 to 100 mass% relative to the entire cellulose fibers, for example, 70 to 100 mass% (e.g., 70 to 98 mass%), preferably 80 to 100 mass% (e.g., 80 to 99 mass%), and more preferably 90 to 100 mass%.
[0029] Cellulose may contain non-cellulose components such as hemicellulose and lignin, and in the case of cellulose fibers (particularly, cellulose nanofibers), the proportion of non-cellulose components in the fibrous cellulose is 30 mass% or less, preferably 20 mass% or less, and more preferably 10 mass% or less. The cellulose fibers may be cellulose fibers that are substantially free of non-cellulose components (particularly, cellulose fibers that do not contain non-cellulose components).
[0030] The degree of polymerization of cellulose may be 500 or more, and preferably 600 or more (for example, about 600 to 100,000), and in the case of nanofibers, the viscosity average degree of polymerization may be, for example, 100 to 10,000, preferably 200 to 5,000, and more preferably 300 to 2,000.
[0031] The viscosity average degree of polymerization can be measured by the viscosity method described in TAPPI T230. That is, 0.04 g of modified cellulose fiber (or raw cellulose fiber) is precisely weighed, 10 mL of water and 10 mL of 1 M copper ethylenediamine aqueous solution are added, and the mixture is stirred for about 5 minutes to dissolve the modified cellulose. The obtained solution is placed in an Ubbelohde type viscosity tube, and the flow rate is measured at 25°C. A mixture of 10 mL of water and 10 mL of 1 M copper ethylenediamine aqueous solution is measured as a blank. Using the intrinsic viscosity [η] calculated based on these measured values, the viscosity average degree of polymerization can be calculated according to the following formula described in the Wood Science Experiment Manual (edited by the Japan Wood Research Society, Bun'ei-do Publishing).
[0032] Viscosity average degree of polymerization = 175×[η].
[0033] The fiber diameter of the cellulose fibers may be on the order of microns or may be on the nanometer size.
[0034] Specifically, the average fiber diameter of the cellulose fibers can be selected from the range of about 3 nm to 100 μm, for example, 4 nm to 50 μm, preferably 5 nm to 30 μm, and more preferably 10 nm to 20 μm. When the cellulose fibers are on the order of microns, the average fiber diameter of the cellulose fibers may be, for example, 1 to 100 μm, preferably 3 to 50 μm, more preferably 5 to 30 μm, and more preferably 10 to 20 μm. When the cellulose fibers are nanometer-sized, the average fiber diameter of the cellulose fibers may be, for example, 1 to 1000 nm, preferably 3 to 500 nm, more preferably 5 to 300 nm, and more preferably 10 to 100 nm. If the fiber diameter is too small, when the cellulose fibers are blended into a resin as a reinforcing material, it may be difficult to disperse the cellulose fibers uniformly in the resin, or it may be difficult to prepare the cellulose fibers themselves. Conversely, if the fiber diameter is too large, there is a risk that the mechanical properties of the resin as a reinforcing material cannot be improved.
[0035] The average fiber length of the cellulose fibers can be selected, for example, from the range of about 0.01 to 500 μm (particularly, 0.1 to 400 μm), and is usually 1 μm or more (e.g., 5 to 300 μm), preferably 10 μm or more (e.g., 20 to 200 μm), and more preferably 30 μm or more (particularly, 50 to 150 μm). If the average fiber length is too short, the mechanical properties of the resin may be reduced, and conversely, if it is too long, the dispersibility in the resin may be reduced.
[0036] The ratio of the average fiber length to the average fiber diameter of the cellulose fibers (aspect ratio) may be, for example, 1.5 or more (e.g., 1.5 to 10,000), preferably 2 or more (e.g., 2 to 1,000), more preferably 2.5 or more (e.g., 2.5 to 500), particularly 3 or more (e.g., 3 to 100), 4 or more (e.g., 4 to 50), or even 5 or more (e.g., 5 to 10). If the aspect ratio is too small, the reinforcing effect on the resin decreases, and conversely, if it is too large, uniform dispersion becomes difficult and the fibers may be easily decomposed (or damaged).
[0037] In this specification and claims, the average fiber diameter, average fiber length and aspect ratio of cellulose fibers may be calculated by averaging 50 fibers randomly selected from an image taken using a scanning electron microscope.
[0038] When the cellulose fibers are nanofibers, they can be prepared by defibrating the cellulose raw material to a fiber diameter of nanometer size using a conventional method, for example, a physical or mechanical method such as a high-pressure homogenizer method, an underwater counter-collision method, a grinder method, a ball mill method, or a biaxial kneading method, or a chemical method using a TEMPO catalyst, phosphoric acid, a dibasic acid, sulfuric acid, hydrochloric acid, or the like.
[0039] (Modifier) The modified cellulose contains 3HB as a modifying agent (esterifying agent), and 3HB or its oligomer (hereinafter sometimes referred to as "(poly)3HB") is chemically bonded to the cellulose. (Poly)3HB may be chemically bonded to any of the hydroxyl groups at the 2-, 3-, or 6-positions of the anhydroglucose unit (or glucose unit), which is a repeating unit of cellulose, but from the viewpoint of productivity, etc., it is preferable that the (poly)3HB is ester-bonded to at least the 6-position.
[0040] 3HB may be an optical isomer (R or S isomer) or may be a racemate, but from the viewpoint of biodegradability, it is preferable to contain at least the R isomer (R-3-hydroxybutyric acid). The ratio of the R isomer in 3HB, i.e., the optical purity (enantiomer or optical isomer excess), is, for example, 50% ee or more (e.g., 80% ee or more), preferably 90% ee or more (e.g., 95 to 100% ee), and more preferably 98 to 100% ee (e.g., 99 to 100% ee, particularly substantially 100% ee). If the optical purity is too low, there is a risk of reduced biodegradability. Note that, as for 3HB, a commercially available product may be used, or 3HB produced by fermentation using a microorganism using a biomass raw material (a biological resource) may be used.
[0041] The average degree of polymerization of (poly)3HB may be 1 or more, and is, for example, 1 to 100, preferably 1 to 10 (e.g., 2 to 5), further preferably 1.5 to 5, more preferably 2 to 4.5, and most preferably 3 to 4. If the average degree of polymerization of (poly)3HB is too low, there is a risk that the effect of modification by (poly)3HB will not be manifested, and conversely, if it is too high, there is a risk that the function as a reinforcing material will be reduced.
[0042] In this specification and claims, the average degree of polymerization of (poly)3HB refers to the average degree of polymerization of the portions grafted to the hydroxyl groups of the cellulose fibers, and can be calculated using NMR, and more specifically, can be measured by the method described in the examples below.
[0043] The grafting rate with (poly)3HB may be 1 mol% or more, for example, 1 to 80 mol%, preferably 3 to 50 mol%, further preferably 5 to 30 mol%, more preferably 7 to 20 mol%, and most preferably 10 to 15 mol%. If the grafting rate is too low, there is a risk that the effect of modification with (poly)3HB will not be manifested.
[0044] In the present specification and claims, the grafting ratio of (poly)3HB means the ratio of (poly)3HB (graft chain) per anhydroglucose unit of cellulose fiber [the grafting ratio of (poly)3HB bonded to the hydroxyl group of anhydroglucose unit via ester bond]. The grafting ratio of (poly)3HB can be calculated using NMR, and in detail, can be measured by the method described in the examples below.
[0045] The modified cellulose may be further modified with other modifying agents (modifying agents other than (poly)3HB) in addition to (poly)3HB.
[0046] Examples of other modifiers (esterifying agents) include carboxylic acids, other hydroxyalkanoic acids (alkanoic acids other than 3HB) or oligomers thereof, and oligomers of 3HB and other hydroxyalkanoic acids.
[0047] Examples of the carboxylic acid include monocarboxylic acids or their anhydrides [for example, aliphatic monocarboxylic acids such as (anhydrous) acetic acid, (anhydrous) propionic acid, (anhydrous) butyric acid, (anhydrous) isobutyric acid, (anhydrous) valeric acid, ethanoic acid propionic anhydride, (anhydrous) (meth)acrylic acid, (anhydrous) crotonic acid, and (anhydrous) oleic acid; alicyclic carboxylic acids such as (anhydrous) cyclohexane carboxylic acid and (anhydrous) tetrahydrobenzoic acid; benzoic acid and (anhydrous) 4-methylbenzoic acid, etc. (Aromatic monocarboxylic acid anhydride, etc.)], dicarboxylic acids (for example, aliphatic dicarboxylic acids such as succinic acid, adipic acid, maleic acid, itaconic acid, etc.; alicyclic dicarboxylic acids such as 1-cyclohexene-1,2-dicarboxylic acid, hexahydrophthalic acid, methyltetrahydrophthalic acid, etc.; aromatic dicarboxylic acids such as phthalic acid, naphthalic acid, etc.), polycarboxylic acids [for example, (anhydrous) polycarboxylic acids such as trimellitic acid, trimellitic anhydride, pyromellitic anhydride, etc.].
[0048] Other hydroxyalkanoic acids include, for example, glycolic acid, 2-hydroxypropanoic acid (lactic acid), 3-hydroxypropanoic acid, 2-hydroxybutanoic acid (2-hydroxybutyric acid), 4-hydroxybutanoic acid, 3-hydroxy-3-methyl-butanoic acid, 2-hydroxypentanoic acid (2-hydroxyvaleric acid), 3-hydroxypentanoic acid, 5-hydroxypentanoic acid, 2-hydroxy-2-methyl-pentanoic acid, 3-hydroxyhexanoic acid, 6-hydroxy-heptanoic acid, 3-hydroxyheptanoic acid, 7-hydroxyheptanoic acid, 3-hydroxyoctanoic acid, 8-hydroxyoctanoic acid, 3-hydroxynonanoic acid, 9-hydroxynonanoic acid, 3-hydroxydecanoic acid, 10-hydroxydecanoic acid, etc. 1-6 Hydroxy C, optionally having an alkyl group 2-15 Other hydroxyalkanoic acids may be the corresponding lactones.
[0049] The ratio of the other modifier may be 100 parts by mass or less (e.g., 0.01 to 100 parts by mass) relative to 100 parts by mass of (poly)3HB, and is, for example, 50 parts by mass or less, preferably 30 parts by mass or less, more preferably 10 parts by mass or less, and most preferably 0 part by mass. If the ratio of the other modifier is too high, there is a risk of biodegradability decreasing.
[0050] (Characteristics of modified cellulose) The form of the modified cellulose of the present disclosure is not particularly limited, and may be in the form of a dispersion, but is usually in the form of a powder, which is easy to handle. Furthermore, since the (poly)3HB bonded to the modified cellulose has high affinity or miscibility with various organic media (including resins), the modified cellulose exhibits high dispersibility in resins and has high reinforcing properties. Therefore, the modified cellulose of the present disclosure is useful as a reinforcing material for resins.
[0051] [Method of manufacturing modified cellulose] The modified cellulose of the present disclosure is obtained by esterifying cellulose fibers (raw cellulose fibers) with 3HB (raw 3HB).
[0052] In the method for producing modified cellulose, the proportion of raw material 3HB can be selected from the range of about 50 to 10,000 parts by mass per 100 parts by mass of raw material cellulose fiber depending on the desired degree of modification, and is, for example, 100 to 5,000 parts by mass, preferably 150 to 4,000 parts by mass, and more preferably 200 to 3,000 parts by mass.
[0053] The reaction between the raw cellulose fiber and the raw 3HB may be carried out in the absence or presence of a catalyst. The modified cellulose of the present disclosure can sufficiently esterify 3HB even in the absence of a catalyst, but a catalyst may be used to adjust the polymerization degree and grafting rate of (poly)3HB. From the viewpoints of excellent operability and suppression of coloration, it is preferable to carry out the reaction in the absence of a catalyst.
[0054] As the catalyst, a conventional esterification catalyst can be used. The conventional esterification catalyst may be a base catalyst or an acid catalyst.
[0055] Examples of the base catalyst include alkali metal hydroxides such as lithium hydroxide, sodium hydroxide, and potassium hydroxide; alkali metal carbonates such as lithium carbonate, sodium carbonate, and potassium carbonate; alkali metal hydrogen carbonates such as sodium hydrogen carbonate and potassium hydrogen carbonate; alkaline earth metal hydroxides such as magnesium hydroxide and calcium hydroxide; alkaline earth metal carbonates such as magnesium carbonate; alkaline earth metal hydrogen carbonates such as magnesium hydrogen carbonate; ammonia; trimethylamine, triethylamine, and other tri-C 1-4 Examples of the amine include tertiary amines such as alkylamines; and heterocyclic amines such as 4-dimethylaminopyridine, morpholine, and piperidine.
[0056] Examples of the acid catalyst include inorganic acids such as sulfuric acid, hydrogen chloride (or hydrochloric acid), nitric acid, and phosphoric acid; and organic acids such as sulfonic acids (alkanesulfonic acids such as methanesulfonic acid, ethanesulfonic acid, and trifluoromethanesulfonic acid; arenesulfonic acids such as benzenesulfonic acid, p-toluenesulfonic acid, and naphthalenesulfonic acid).
[0057] The amount of the catalyst used is, for example, 0.01 to 100 parts by mass, preferably 0.05 to 50 parts by mass, and more preferably 0.1 to 30 parts by mass, relative to 100 parts by mass of the cellulose fibers.
[0058] The reaction may be carried out in the absence of an organic solvent or in the presence of an organic solvent. Examples of the organic solvent include alcohols (C 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 220, 230, 240, 250, 260, 270, 280, 290, 300, 310, 320, 330, 340, 350, 360, 370, 380, 390, 400, 410 1-4alkanols, etc.), ethers (cyclic ethers such as dioxane and tetrahydrofuran), ketones (acetone, etc.), amides (dimethylformamide, diethylformamide, dimethylacetamide, diethylacetamide, etc.), pyrrolidones (N-methyl-2-pyrrolidone, etc.), sulfoxides (dimethyl sulfoxide, etc.), alkanediols (e.g., C such as ethylene glycol and propylene glycol, 2-4 alkanediols), cellosolves (methyl cellosolve, ethyl cellosolve), carbitols (ethyl carbitol, etc.), carbonates (ethylene carbonate, propylene carbonate, dimethyl carbonate, etc.), etc. These solvents may be used alone or in combination of two or more.
[0059] In the modified cellulose of the present disclosure, cellulose can be sufficiently esterified with 3HB even in the absence of an organic solvent, and therefore, from the standpoint of operability, etc., it is preferable to carry out the reaction in the absence of an organic solvent.
[0060] The reaction may be carried out under normal pressure, elevated pressure, or reduced pressure, but is preferably carried out under reduced pressure in order to improve the reactivity. The reduced pressure (gauge pressure) is, for example, 10 to 300 kPa, preferably 30 to 200 kPa, and more preferably 50 to 150 kPa.
[0061] The reaction temperature is, for example, 50 to 200° C., preferably 70 to 180° C., more preferably 80 to 150° C., and more preferably 100 to 130° C. The reaction time is, for example, 10 minutes to 48 hours, preferably 30 minutes to 24 hours, more preferably 1 to 12 hours, and more preferably 2 to 8 hours. The reaction can be carried out in air or in an inert gas (nitrogen gas, rare gas such as argon gas, etc.) atmosphere with mixing or stirring.
[0062] As a method of mixing or stirring, the components may be kneaded by a conventional mixing or stirring means at a rotation speed of, for example, about 10 to 2000 rpm, preferably 20 to 1500 rpm, more preferably 30 to 1000 rpm, and particularly preferably about 50 to 500 rpm. Examples of the conventional mixing or stirring method include a method using a ball mill, a tumble mixer, a ribbon blender, a Henschel mixer, a mixing roller, a kneader, a Banbury mixer, an extruder (such as a single-screw or twin-screw extruder), and the like.
[0063] The modified cellulose produced by the reaction may be separated and purified by a conventional method (e.g., centrifugation, filtration, concentration, extraction, etc.). For example, a solvent capable of dissolving at least 3HB may be added to the reaction mixture, and unreacted 3HB may be removed by a separation method (conventional method) such as centrifugation, filtration, extraction, etc., to separate and purify the cellulose. The separation operation may be carried out multiple times (e.g., about 2 to 5 times). Furthermore, the separated and purified modified cellulose may be dried under reduced pressure or normal pressure at room temperature or under heating to obtain modified cellulose in a powder form.
[0064] Furthermore, when the modified cellulose that has been purified by repeatedly removing unreacted 3HB using the above-mentioned separation method or the like is analyzed using a method such as FT-IR analysis, a peak derived from an ester bond and a peak derived from 3HB are present, confirming that 3HB is bonded to the cellulose.
[0065] [Resin composition] The resin composition of the present disclosure contains the modified cellulose and at least one resin selected from a thermoplastic resin and a curable resin.
[0066] Examples of thermoplastic resins include polyolefin resins, styrene resins, acrylic resins, vinyl chloride resins, polyvinyl alcohol resins, polyacetal resins, polyester resins, polycarbonate resins, polyamide resins, polyimide resins, polysulfone resins, polyphenylene ether resins, polyphenylene sulfide resins, fluororesins, cellulose derivatives (excluding the modified cellulose of the present disclosure), etc. These thermoplastic resins can be used alone or in combination of two or more.
[0067] Examples of the curable resin include phenol resin, melamine resin, urea resin, benzoguanamine resin, silicone resin, epoxy resin, unsaturated polyester resin, vinyl ester resin, polyurethane resin, etc. These curable resins can be used alone or in combination of two or more kinds.
[0068] Among these, thermoplastic resins are preferred from the viewpoint of moldability, etc., and thermoplastic resins having ester bonds and / or carbonate bonds (e.g., polyalkylene arylate-based resins such as polyethylene terephthalate; polycarbonate-based resins such as bisphenol A polycarbonate, etc.) are more preferred from the viewpoint of excellent affinity with modified cellulose, with polyester-based resins being the most preferred.
[0069] Examples of polyester resins include polyester resins and polyester carbonate resins. Among these, polyester resins are preferred because of their excellent affinity with modified cellulose, and homopolymers or copolymers of at least one monomer selected from hydroxyalkanoic acid and lactone are particularly preferred. Examples of hydroxyalkanoic acid include the hydroxyalkanoic acids exemplified in the section on the modifier for modified cellulose.
[0070] Since the modified cellulose of the present disclosure has excellent biodegradability, the resin is preferably a biodegradable plastic. Examples of biodegradable plastics include polyvinyl alcohol-based resins, polyether-based resins, aliphatic polyester-based resins, aliphatic polyamide-based resins, and cellulose derivatives (excluding the modified cellulose of the present disclosure). Among these, aliphatic polyester-based resins are preferred because of their excellent affinity with the modified cellulose.
[0071] Examples of aliphatic polyester resins include polyhydroxyalkanoates (PHAs) such as polylactic acid (PLA), poly3-hydroxybutyrate (PHB), 3-hydroxybutyrate-3-hydroxyhexanoate copolymer (PHBH), and polyhydroxyvaleric acid; polymers of aliphatic dicarboxylic acids and aliphatic diols such as polyethylene adipate and polybutylene succinate (PBS); and lactone ring-opening polymers such as polycaprolactone (PCL). These aliphatic polyester resins can be used alone or in combination of two or more.
[0072] Of these aliphatic polyester resins, PHA is preferred because of its high affinity with modified cellulose, and biodegradable resins containing 3HB (particularly, R-3HB) homopolymers or copolymers (e.g., PHB, PHBH, etc.) are more preferred because of their high biodegradability even under anaerobic conditions, and 3HB copolymers such as PHBH are most preferred because of their excellent balance of various properties such as mechanical properties.
[0073] The molecular weight of the thermoplastic resin (particularly, PHA such as PHBH) is not particularly limited, and is preferably expressed as a weight average molecular weight (unit: × 10 4 ) is, for example, about 0.1 to 100, preferably about 1 to 80, and more preferably about 2 to 70; number average molecular weight (unit: × 10 4 ) may be, for example, 0.1 to 100, preferably 1 to 80, and more preferably 2 to 70, and the dispersity (M w / M n ) may be, for example, 1 to 5, preferably 1 to 3, more preferably 1 to 2, and particularly preferably 1 to 1.5.w ) and number average molecular weight (M n ) can be measured in terms of polystyrene by GPC (Gel Permeation Chromatography).
[0074] The proportion of modified cellulose can be selected from the range of about 0.01 to 100 parts by mass relative to 100 parts by mass of the resin (particularly PHA such as PHBH), and is, for example, 0.05 to 30 parts by mass, preferably 0.1 to 20 parts by mass, further preferably 0.2 to 10 parts by mass, more preferably 0.3 to 5 parts by mass, and most preferably 0.5 to 3 parts by mass. If the proportion of modified cellulose is too low, there is a risk that the effect as a reinforcing material will not be exhibited, and conversely, if it is too high, there is a risk that the mechanical properties will decrease.
[0075] The resin composition may further contain various additives [e.g., plasticizers, flame retardants, stabilizers (thermal stabilizers, antioxidants, ultraviolet absorbers, etc.), colorants (pigments, etc.), fillers, antistatic agents, lubricants, release agents, antibacterial agents, antifungal agents, etc.] as necessary. These additives may be used alone or in combination of two or more. The total ratio of these additives can be selected according to the type of additive, and the total amount of the additives can be selected from the range of 0.001 to 100 parts by mass relative to 100 parts by mass of the resin, and is, for example, 100 parts by mass or less (e.g., 0.01 to 80 parts by mass), preferably 70 parts by mass or less (e.g., 0.1 to 60 parts by mass), and more preferably 50 parts by mass or less (e.g., 0.1 to 40 parts by mass).
[0076] Molded articles made of the resin composition have excellent mechanical properties, and for example, in a resin composition containing 2% by mass of modified cellulose, the Young's modulus in a tensile test may be 1200 MPa or more, for example, 1200 to 2000 MPa, preferably 1230 to 1500 MPa, and more preferably 1250 to 1300 MPa. In addition, in a resin composition containing 2% by mass of modified cellulose, the elongation at break in a tensile test may be 10% or more, for example, 10 to 50%, preferably 12 to 40%, and more preferably 13 to 30%.
[0077] In this specification and claims, the maximum stress and elongation at break in a tensile test can be measured by the method described in the examples below.
[0078] The resin composition can be molded into a predetermined shape such as a wire, a film or sheet, a cylinder or pipe, or a three-dimensional shape such as a casing or a housing by a conventional molding method (such as a melt molding method such as a hot press molding method, an extrusion molding method, an injection molding method, or a calendar molding method, or a casting method). The molding temperature is, for example, 130 to 230° C., preferably 140 to 200° C., further 150 to 190° C., and more preferably 160 to 180° C. In molding, pressure may be applied, and the pressure is, for example, 1 to 100 MPa, preferably 5 to 50 MPa, and further preferably 10 to 30 MPa. EXAMPLES
[0079] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. The raw materials and evaluation methods used are as follows.
[0080] (raw materials) Cellulose: Cellulose powder manufactured by Nacalai Tesque, Inc., product number 07748-75, average fiber diameter 12.6 μm, average fiber length 77.3 μm (average fiber diameter and average fiber length are the average values of 20 measurements taken using a scanning electron microscope)
[0081] 3HB: R-3-hydroxybutyric acid synthesized by the following method (3HB synthesis method) An aqueous solution of R-3-hydroxybutyric acid produced according to the method described in Example 1 of JP 2019-176839 A was concentrated until no water was released using an evaporator set at 70° C. 30% by mass of ethyl acetate and about 0.1% by mass of seed crystals of R-3-hydroxybutyric acid were added to the obtained concentrated liquid, which was then left overnight at 4° C., filtered, and dried.
[0082] PHBH: Manufactured by Kaneka Corporation, product name "AONILEX X131A".
[0083] (FT-IR analysis) The molecular structure and introduction of functional groups of the raw material 3HB, raw material cellulose, and modified cellulose were measured before and after the reaction using an FT-IR analyzer, and the introduction of 3HB was confirmed. The FT-IR analyzer used was a Nicoleti S5 spectrometer (Thermo Fisher SCIENTIFIC Co., Ltd.) equipped with an iD5ATR attachment. The measurement range was 4000 to 400 cm. -1 It was decided.
[0084] (Modified cellulose grafting rate) Modified cellulose, solid 13 For C-NMR, a Bruker AVANCE III WB (manufactured by BRUKER) was used. 13 The quantitative analysis was performed as C. 13 The C-NMR spectrum chart is shown, and the grafting ratio was calculated based on a comparison between the carbon amount of C7,11 (value based on integrated intensity) and the carbon amount of C1. That is, since the 3HB bonded to cellulose is an oligomer, the number of graft chains was calculated by the carbon amount of C7,11 / (n+1) (n+1 indicates the average degree of polymerization of 3HB), and compared with the carbon amount of C1, which corresponds to the number of glucose units in the cellulose main chain. In detail, the grafting ratio was calculated as the carbon amount of C7,11 / (n+1) / carbon amount of C1 × 100%.
[0085] (Average degree of polymerization of 3HB, n+1) Modified cellulose, solid 13 For C-NMR, a Bruker AVANCE III WB (manufactured by BRUKER) was used. 13 Quantitative analysis was performed to measure the average degree of polymerization (n+1) of 3HB.
[0086] (Tensile test) The resin composition was measured for Young's modulus, maximum stress, and breaking point elongation using a small tabletop testing machine (Shimadzu Corporation, "EZ-Graph") in accordance with JIS K 7161. The test conditions were a crosshead speed of 10 mm / min, a test piece length of 20 mm, a width of 2 mm, and a thickness of approximately 0.1 mm. A load cell of 100 N was used.
[0087] Example 1 1g of cellulose and 5g of 3HB were mixed and reacted for 4 hours at 110℃ and -97kPa(G). An excess amount of methanol was added to the reaction mixture, which was then stirred and filtered. An excess amount of chloroform was then added, stirred, filtered, and dried under reduced pressure at room temperature to obtain powdered 3HB-modified cellulose (3HB-C).
[0088] Example 2 3HB-C was obtained by reaction and washing under the same conditions as in Example 1, except that the amount of 3HB was changed to 10 g.
[0089] Example 3 3HB-C was obtained by reaction and washing under the same conditions as in Example 1, except that the amount of 3HB was changed to 15 g.
[0090] Example 4 3HB-C was obtained by reaction and washing under the same conditions as in Example 1, except that the amount of 3HB was changed to 30 g.
[0091] Example 5 3HB-C was obtained by reaction and washing under the same conditions as in Example 2, except that the reaction time was changed to 2 hours.
[0092] Example 6 The reaction and washing were carried out under the same conditions as in Example 2, except that the reaction time was changed to 8 hours, to obtain 3HB-C.
[0093] The results of FT-IR analysis of the 3HB-C obtained in Examples 1 to 6 are shown in FIG. 1 together with the results for the raw material 3HB and the raw material cellulose. As is clear from FIG. 1, the 3HB-C obtained in Examples 1 to 6 has a peak at 1700 cm derived from the carboxylic acid of 3HB.-1 The peak around 1730 cm has disappeared. -1 Since a peak derived from an ester was observed in the vicinity, it was confirmed that 3HB and cellulose formed an ester.
[0094] Furthermore, for 3HB-C obtained in Examples 1 to 6, 13 The grafting rate and average degree of polymerization were calculated from C-NMR, and the results are shown in Table 1.
[0095] [Table 1]
[0096] In addition, solid 13 The results of C-NMR confirmed that the modified cellulose obtained in Examples 1 to 6 had 3HB bonded to the 6th carbon position (C6) of the anhydroglucose unit at a grafting rate of about 7 to 15% and an average degree of polymerization of about 3 to 4.
[0097] Comparative Example 1 The PHBH was hot pressed at 170°C and 20 MPa to obtain a film for tensile testing.
[0098] Comparative Example 2 0.01g of raw cellulose and 1.99g of PHBH were added to chloroform, stirred, and reprecipitated by adding an excess amount of methanol. The precipitate was filtered and dried under reduced pressure at room temperature (about 20°C) to obtain a cellulose / PHBH composite powder. This powder was then hot pressed at 170°C and 20 MPa to obtain a film for tensile testing.
[0099] Comparative Example 3 A film for tensile testing was obtained in the same manner as in Comparative Example 2, except that the amount of raw cellulose was 0.02 g and the amount of PHBH was 1.98 g.
[0100] Comparative Example 4 A film for tensile testing was obtained in the same manner as in Comparative Example 2, except that the amount of raw cellulose was 0.04 g and the amount of PHBH was 1.96 g.
[0101] Example 7 0.01 g of 3HB-C and 1.99 g of PHBH obtained in Example 2 were put into chloroform, stirred, and an excess amount of methanol was added to reprecipitate. The precipitate was filtered and dried under reduced pressure at room temperature to obtain a 3HB-C / PHBH composite powder. Next, this powder was hot pressed at 170°C and 20 MPa to obtain a film for tensile testing.
[0102] Example 8 A film for tensile testing was obtained in the same manner as in Example 7, except that the amount of 3HB-C was 0.02 g and the amount of PHBH was 1.98 g.
[0103] Example 9 A film for tensile testing was obtained in the same manner as in Example 7, except that the amount of 3HB-C was 0.04 g and the amount of PHBH was 1.96 g.
[0104] The films obtained in Examples 7 to 9 and Comparative Examples 1 to 4 were subjected to a tensile test, and the results are shown in Table 2.
[0105] [Table 2]
[0106] As is clear from the results in Table 2, the composite films of the Examples had improved Young's modulus and maximum stress compared to Comparative Example 1, which did not contain cellulose. In addition, a comparison between Comparative Examples 2 to 4 and Examples 7 to 9 shows that the Young's modulus, maximum stress, and elongation at break were all improved by modifying cellulose. That is, the results of the tensile test clearly show that the 3HB-C / PHBH composite film has improved elastic modulus, strength, and elongation at break compared to the raw cellulose / PHBH composite material. FIG. 3 shows the results of the tensile test of the composite films obtained in Comparative Examples 1 to 2 and Example 7, FIG. 4 shows the results of the tensile test of the composite films obtained in Comparative Examples 1, 3, and Example 8, and FIG. 5 shows the results of the tensile test of the composite films obtained in Comparative Examples 1, 4, and Example 9. In all of these figures, it is easy to see that the tensile properties are improved by modifying cellulose.
[0107] FIG. 6 shows SEM photographs of the tensile fracture surfaces of the composite films obtained in Example 8 (PHBH / 3HB-C) and Comparative Example 4 (PHBH / raw cellulose). Enlarged views are also provided for both the Examples and Comparative Examples so that the interface can be clearly seen. As is clear from FIG. 6, in Comparative Example 4, peeling occurred at the interface between the raw cellulose and PHBH, but in Example 8, no such peeling was observed at the interface between 3HB-C and PHBH. For example, in the enlarged view of the photograph of Example 8, in which 3HB-C was blended, it can be clearly observed that the interface between 3HB-C and PHBH is compatible, whereas in the enlarged view of the photograph of Comparative Example 4, a large void gap is generated at the interface. In other words, it was found that by modifying 3HB to cellulose, 3HB (oligomer) on the surface of the cellulose functions as a compatibilizer. [Industrial Applicability]
[0108] The modified cellulose of the present disclosure can be used as an additive for resins, particularly as a reinforcing material. The resin composition of the present disclosure can be used to form various molded articles such as daily necessities, electrical and electronic devices, and building materials, depending on the type of resin. In particular, when used as a reinforcing material for biodegradable plastics, the modified cellulose exhibits biodegradability under aerobic and anaerobic conditions (particularly under anaerobic conditions), and therefore the resin composition containing the modified cellulose fiber is useful for disposable products such as tableware (straws, cups, plates, chopsticks, spoons, forks, etc.), packaging materials (e.g., containers for food, daily necessities, electrical and electronic devices and parts, bags such as plastic shopping bags, Eco Bags (registered trademark), and garbage bags), etc.
Claims
1. A modified cellulose in which 3-hydroxybutyric acid or its oligomer having an average degree of polymerization of 1.5 or more is bonded to cellulose fibers.
2. 2. The modified cellulose according to claim 1, wherein the 3-hydroxybutyric acid or an oligomer thereof is ester-bonded to the 6-position of the anhydroglucose unit of the cellulose fiber.
3. 3. The modified cellulose according to claim 1, wherein the average degree of polymerization of said 3-hydroxybutyric acid or its oligomer is from 1.5 to 10.
4. The modified cellulose according to any one of claims 1 to 3, wherein a grafting rate of the 3-hydroxybutyric acid or an oligomer thereof is from 5 to 30 mol %.
5. The modified cellulose according to any one of claims 1 to 4, wherein the 3-hydroxybutyric acid is R-3-hydroxybutyric acid.
6. A resin composition comprising the modified cellulose according to any one of claims 1 to 5 and at least one resin selected from the group consisting of thermoplastic resins and curable resins.
7. The resin composition according to claim 6 , wherein the resin comprises a biodegradable plastic.
8. 8. The resin composition according to claim 6, wherein the resin is a homopolymer or copolymer of at least one monomer selected from the group consisting of hydroxyalkanoic acids and lactones.
9. The resin composition according to any one of claims 6 to 8, wherein the proportion of the modified cellulose is 0.1 to 20 parts by mass per 100 parts by mass of the resin.
10. A method for improving mechanical properties of a resin by blending the modified cellulose according to any one of claims 1 to 5 with the resin.
11. The method according to claim 10, wherein the resin is a biodegradable plastic.
Citation Information
Patent Citations
Method of manufacturing thermoplastic cellulose ester based multifilament
JP2003013324A
Modified nanocellulose, and resin composition containing modified nanocellulose
JP2014148629A
Modified cellulose and manufacturing method therefor
JP2016079369A
Biodegradable copolymer and production process therefor as well as biodegradability improvement method
JP2017025138A
Masterbatch containing acylation modified microfibrillated vegetable fiber
JP2017171713A